Regional Disaster Management Agency Strategy In Flood Disaster Mitigation In Bontang City, East Kalimantan Province - Remon Samosir; Mujahidin; Lalu Ahmad Murdhani (International Journal of Scientific Research, 2024)
The research entitled "Regional Disaster Management Strategies in Mitigating Flood Disasters in the City of Bontang, Province of East Kalimantan" based on the events of the flood disaster that hit the City of Bontang, it is known that it is a natural disaster that often occurs compared to other natural disasters. So the Regional Disaster Management Agency needs to immediately improve flood management based on the mitigation aspect by evaluating and analyzing appropriate and fast strategies according to the existing conditions in the City of Bontang so that they can find out the right efforts and the constraints that affect them so that they can maximally reduce the risk of flood disasters efficiently and effective. This study aims to determine the strategies, constraints, and efforts of the Regional Disaster Management Agency in tackling floods in the city of Bontang through mitigation activities. Through analyzing Kooten's strategy theory using descriptive qualitative research methods and inductive approaches through data collection techniques namely interviews, observation, and documentation as well as data analysis techniques using triangulation techniques by testing the validity of the data that has been collected and through the stages of data reduction, data presentation, and withdrawal conclusion. Based on the results of the analysis it was concluded that the mitigation strategy of the Regional Disaster Management Agency in the city of Bontang has carried out a good strategy in several indicators, but there are obstacles that have caused the mitigation strategy to not be optimally implemented. So the authors suggest that the Regional Disaster Management Agency in the city of Bontang can continue to improve institutional quality in evaluating appropriate mitigation strategies according to existing conditions in various aspects.